0678 Slow Wave Sleep Recovery Correlates with Brain Functional and Structural Changes in Alcohol Use Disorder. (25th May 2022) - Zhang, Rui; Tomasi, Dardo; Shokri-Kojori, Ehsan; Manza, Peter; Feldman, Dana; Kroll, Danielle; Biesecker, Caterine; McPherson, Katherine; Wang, Gene-Jack; Wiers, Corinde; Volkow, Nora
Abstract: Introduction: Sleep disturbances are very common in alcohol use disorder (AUD) and contribute to relapse. Recovery of N3 sleep within the first 30 days of abstinence is limited. Brain mechanisms associated with N3 sleep recovery in AUD are still poorly understood. Methods: We examined brain functional and structural changes associated with inter-individual differences in N3 recovery in 30 AUD patients (9 Females, mean age: 41 years) undergoing a 3-week inpatient detoxification. We measured patients' N3 sleep, resting state functional connectivity (RSFC), grey matter volume (GMV) and negative mood on week 1 and week 3. Results: AUD patients had shorter N3 sleep than healthy controls on week 1 and showed a trend towards N3 sleep recovery after 3-week detoxification. Inter-individual differences in N3 recovery were observed. Larger increases in N3 sleep were associated with greater improvement in negative mood. Inter-individual variations in N3 recovery were associated with increases in midline default mode network (DMN) RSFC and anterior DMN GMV. Exploratory analyses revealed significant sex effects on N3 sleep and N3 recovery such that AUD females had greater N3 impairments on week 1 and greater N3 recovery after detoxification than AUD males. Conclusion: We show a significant relationship between N3 recovery and structural and functional changes in DMN in AUD patients during detoxification. Combining nighttime and daytime interventions that target N3 sleep and DMN might have a complementary therapeutic effect on AUD recovery including mood improvement. Future investigations on sex differences with a larger sample and with longitudinal data for a longer period of abstinence are needed. Support (If Any):